Evaluación del daño genotóxico mediante ensayo de cometa en población expuesta a material particulado MP 25 en la zona Sur de ciudad de CuencaEcuador - Barrera Parra, Diana Alexandra (2018)
Abstract:Environmental pollution is a problem of great interest worldwide because exposure to chemicals produces harmful effects on health such as respiratory problems, cardiovascular and cancer. The air quality in the city of Cuenca shows high concentrations of particle matter 2.5 (PM 2.5) in the urban area, caused mainly by the high vehicular traffic responsible for the emission of air pollutants with indirect genotoxic effects. In the present work, the genotoxic damage produced by exposure to high and low concentrations of PM 2.5 was evaluated, the test was performed with persons who reside or work in the southern area of the city of Cuenca using the comet assay. There was a significant increase in the mean of the genotoxic damage index and the length of the tail of the comet (p< 0.05), there were statistical differences between the analyzed groups, indicating that exposure to high concentrations of PM 2.5 produces DNA damage of the cells which could increase the risk of cancer.